Ambulatory emergency oncology: A key tenet of future emergency oncology care. Issue 1 (31st October 2019) - Cooksley, Tim; Marshall, Will; Ahn, Shin; Lasserson, Daniel S.; Marshall, Ernie; Rice, Terry W.; Klotz, Adam
Summary: Ambulatory emergency oncology The challenges of emergency oncology alongside its increasing financial burden have led to an interest in developing optimal care models for meeting patients' needs. Ambulatory care is recognised as a key tenet in ensuring the safety and sustainability of acute care services. Increased access to ambulatory care has successfully reduced ED utilisation and improved clinical outcomes in high‐risk non‐oncological populations. Individualised management of acute cancer presentations is a key challenge for emergency oncology services so that it can mirror routine cancer care. There are an increasing number of acute cancer presentations, such as low‐risk febrile neutropenia and incidental pulmonary embolism, that can be risk assessed for care in an emergency ambulatory setting. Modelling of ambulatory emergency oncology services will be dependent on local service deliveries and pathways, but are key for providing high quality, personalised and sustainable emergency oncology care. These services will also be at the forefront of much needed emergency oncology to define the optimal management of ambulatory‐sensitive presentations.